2021
DOI: 10.1007/s11547-021-01390-4
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional analysis of follow-up chest MRI and chest CT scans in patients previously affected by COVID-19

Abstract: Purpose The aim of the study was to prospectively evaluate the agreement between chest magnetic resonance imaging (MRI) and computed tomography (CT) and to assess the diagnostic performance of chest MRI relative to that of CT during the follow-up of patients recovered from coronavirus disease 2019. Materials and methods Fifty-two patients underwent both follow-up chest CT and MRI scans, evaluated for ground-glass opacities (GGOs), consolidation, interlobul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Data from these countries have proven the benefit of a booster dose in reducing symptomatic infection and offering a significant decrease in critical outcomes [ 49 , 50 , 51 , 52 , 53 , 54 ]. Moreover, the protection level offered by previous SARS-CoV-2 infection, both in terms of infection and disease severity and, therefore, of outcome, is still unclear [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. In this scenario, the main essential element leading to the evolution of SARS-CoV-2 infection is the interaction with the host’s immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Data from these countries have proven the benefit of a booster dose in reducing symptomatic infection and offering a significant decrease in critical outcomes [ 49 , 50 , 51 , 52 , 53 , 54 ]. Moreover, the protection level offered by previous SARS-CoV-2 infection, both in terms of infection and disease severity and, therefore, of outcome, is still unclear [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. In this scenario, the main essential element leading to the evolution of SARS-CoV-2 infection is the interaction with the host’s immune system.…”
Section: Introductionmentioning
confidence: 99%
“…There was 100% sensitivity and 100% specificity for detection of GGOs, septal thickening/reticulations, and pleural thickening on MRI chest with a perfect agreement ( k =1) between the CT and MRI. However, a prospective study from Italy on post-COVID subjects after discharge reported more GGOs and interstitial thickening on MRI than CT with the reported frequency of 94.2% Vs. 76.9%, and 86.5% Vs. 78.8%, for MRI chest and CT chest, respectively ( 13 ). The sensitivity and specificity for GGOs on the MRI chest were 100% (95% CI: 0.91–1.00) and 25% (95% CI: 0.05–0.57), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…TRUFI could detect only 75% of interstitial thickening and 80% GGOs. Pecoraro et al reported false-positive results for GGOs in 9 subjects on MRI chest, and the authors claimed the superior role of MRI with its ability to discriminate the GGOs by quantifying the proton density of alveolar contents ( 13 ). Nevertheless, CT has a high spatial resolution as compared to MRI ( 20 ), and no other studies comparing CT and MRI chest imaging reported higher detection of GGOs on MRI than CT. Rana et al reported false-positive detection of GGOs on T2-W TSE, T2-W MultiVane XD and T1W mDixon sequences in one child; and on SSFP sequence in two subjects ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations